1994
DOI: 10.1093/oxfordjournals.jbchem.a124327
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Induces Different Subunit Organizations and Functional Diversity of Proteasomes1

Abstract: To obtain information on the role of proteasomes in the immune system, we examined the effect of a major immunomodulatory cytokine, gamma interferon (IFN-gamma), on the expressions, structures, and functions of proteasomes. IFN-gamma greatly increased the levels of the mRNAs encoding LMP2 and LMP7, putative immuno-proteasome subunits encoded by genes within the class II MHC region, and these two subunits synthesized were assembled completely into the proteasomal multi-subunit complex in various types of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
282
1
4

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(305 citation statements)
references
References 7 publications
18
282
1
4
Order By: Relevance
“…Since the activity of the total proteasome population changed after incorporation of only small amounts of LMP2 or -7, these subunits must cause major alterations in peptidase activity. Thus, their expression can account for the changes in proteasome activity induced by interferon 7, and these findings lend further support to the proposed roles of LMPs in altering the nature of the peptides generated for antigen presentation.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Since the activity of the total proteasome population changed after incorporation of only small amounts of LMP2 or -7, these subunits must cause major alterations in peptidase activity. Thus, their expression can account for the changes in proteasome activity induced by interferon 7, and these findings lend further support to the proposed roles of LMPs in altering the nature of the peptides generated for antigen presentation.…”
supporting
confidence: 61%
“…These peptideprotein complexes are then transported to the cell surface for presentation to cytotoxic T cells (1,3). Recently, strong evidence has been obtained implicating the proteasome (multicatalytic proteinase complex) and the ATP-ubiquitindependent pathway (4) in the process of the generation of antigenic fragments (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Although the reduction of mRNA precedes the loss of RARγ and RXRα protein, increased protein degradation appears to be involved since a proteasome inhibitor could potently restore the receptor proteins levels. Previous studies have reported that IFNγ increases proteasomal activity [46] but IFNγ also induced a differentiation process resembling an apoptotic pathway [47], which might result in the general loss of proteins. As with PMA, RARα was much less affected than RARγ/RXRα which incriminates proteasomal degradation of the heterodimer due to RA-induced activation [43].…”
Section: Does Ifnγ Impair Retinoid Signalling Due To Reduced Rar-levels?mentioning
confidence: 96%
“…Only three of the ␤ subunits (two copies of each) are proteolytically active: ␦ (␤1), X (␤5), and Z (␤5). In cells stimulated by the proinflammatory cytokine IFN-␥, the composition of the proteasome is altered such that the three active ␤ subunits are replaced by inducible subunits: lmp2 (␤1i), lmp7 (␤5i), and mecl1 (␤2i) (12)(13)(14)(15)(16)(17). This modified proteasome is the immunoproteasome (18).…”
Section: Heat Shock Up-regulates Lmp2 and Lmp7 And Enhances Presentatmentioning
confidence: 99%